Factors involved in maintaining Karnofsky Performance Status (≥ 50%) in glioblastoma, IDH-wildtype patients treated with temozolomide and radiotherapy - Shigeo Ohba; Takao Teranishi; Kazuyasu Matsumura; Masanobu Kumon; Daijiro Kojima; Eiji Fujiwara; Kazutaka Nakao; Kiyonori Kuwahara; Kazuhiro Murayama; Eriel Sandika Pareira; Seiji Yamada; Masahiro Joko; et al. (Scientific Reports)
Abstract Karnofsky Performance Status (KPS) is a widely used scale to assess performance status. KPS ≥ 50% implies that patients can live at home. Therefore, maintaining KPS ≥ 50% is important to improve the quality of life of patients with glioblastoma, whose median survival is less than 2 years. This study aimed to identify the factors associated with survival time with maintenance of KPS ≥ 50% (survival with KPS ≥ 50%) in patients with glioblastoma, IDH-wildtype. Ninety-eight patients with glioblastomas, IDH-wildtype, who were treated with concomitant radiotherapy (RT) and temozolomide (TMZ) followed by maintenance TMZ therapy, and whose KPS at the start of RT was ≥ 50%, were included. The median survival with KPS ≥ 50% was 13.3 months. In univariate analysis, preoperative KPS (≥ 80%), KPS at the start of RT (≥ 80%), residual tumor size (< 2 cm3), methylated MGMT promotor, and implantation of BCNU wafer were associated with survival with KPS ≥ 50%. In multivariate analysis, KPS at the start of RT (≥ 80%), methylated MGMT promotor, and residual tumor size (< 2 cm3) were significantly associated with increased survival with KPS ≥ 50%. A strategy of maximum possible tumor resection without compromising KPS is desirable to prolong the survival time with KPS ≥ 50%.